Development of academic supervision instruments based on differentiated instruction in merdeka curriculum - Rudiyanto; Ngatmini; Joko Sulianto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Academic supervision plays an important role in improving school learning quality. However, its implementation remains suboptimal, particularly regarding the instruments used and their alignment with differentiated instruction in the Merdeka Curriculum. This study aims to develop academic supervision instruments based on differentiated instruction, based on the Merdeka Curriculum. The products include a teaching module review instrument, a classroom observation tool, and a simple digital tool to support their use. The research employed a research and development (R&D) approach with the Borg and Gall model, covering six stages: problem identification, data collection, product design, design validation, design revision, and product testing. The subjects were 10 principals and three expert validators in Dabin II, Subah in Batang Regency. Data were collected using validation questionnaires and user response surveys. Validation results showed all items were rated Good to Excellent with an average score of 0.90, while principal responses indicated very high practicality with an average score of 94.05%. These findings confirm that the developed instruments are valid, practical, and effective in supporting the implementation of differentiated instruction within the Merdeka Curriculum.